Effect of different levels of rumen degradable nitrogen, sulphur and phosphorus on inorganic matter digestibility of paddy straw - RAMACHANDRA, K S; SAMPATH, K T (The Indian Journal of Animal Sciences, 2013)
The supplementation effect of different levels of rumen degradable nitrogen (RDN) and sulphur and phosphorus on the in vitro organic matter digestibility (IVOMD) of paddy straw was studied. Supplementing the straw with a level of 22.5 g RDN/kg DOM through urea increased the OM digestibility of the straw significantly. Increasing the level of RDN to 30 g/kg DOM did not have any additional advantage. Supplementation of sulphur (1.8 and 2.7 g/kg DOM) and phosphorus (4.5 g/kg DOM) either alone or in combination did not have any significant effect. Supplementing sulphur and phosphorus along with supplemental RDN did not cause any further significant improvement on the IVOMD of the straw.